German Debt Traded in London During World War II: A British Perspective on Hitler - William O. Brown Jr.; Richard C.K. Burdekin (Claremont McKenna College, Department of Economics, 1999)
Two series of German bonds, issued in 1924 and 1930, traded on the London Stock Exchange throughout Hitler's 1933-1945 regime in Germany. We isolate both structural breaks and turning points in these bond series. Major turning points follow Hitler's reintroduction of conscription in 1935, the outbreak of war in 1939 and the D-Day invasion of June 1944. The German bonds' sustained downtrend after 1935 suggests that bondholders recognized the negative implications of Hitler's program. Bond prices recover during the war, however, and appear to anticipate the overthrow of Hitler and the postwar settlement of foreign bondholders' claims.
Keywords: N20; N40; 330; bonds; Germany; Hitler